2008
DOI: 10.1007/s00125-008-1041-9
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion in relation to cognitive function and type 2 diabetes

Abstract: Aim/hypothesis Underlying mechanisms for decreased cognitive functioning in patients with type 2 diabetes are unclear. In the general population, cerebral hypoperfusion is a risk factor for cognitive dysfunction and dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 25 publications
4
54
1
2
Order By: Relevance
“…The results did not reach an agreement yet. Some studies have reported decreased CBF in T2DM (Xia et al 2015; Novak et al 2006; Last et al 2007; Nagamachi et al 1994), while others did not observe CBF alteration in T2DM (Tiehuis et al 2008; Rusinek et al 2015; Novak et al 2011). Most of the studies reporting no CBF alteration in T2DM typically used large regions of interest (ROI) and/or did not adequately account for the potential risk factors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results did not reach an agreement yet. Some studies have reported decreased CBF in T2DM (Xia et al 2015; Novak et al 2006; Last et al 2007; Nagamachi et al 1994), while others did not observe CBF alteration in T2DM (Tiehuis et al 2008; Rusinek et al 2015; Novak et al 2011). Most of the studies reporting no CBF alteration in T2DM typically used large regions of interest (ROI) and/or did not adequately account for the potential risk factors.…”
Section: Discussionmentioning
confidence: 98%
“…ASL has been recently used to evaluate CBF in T2DM patients, however the reports are contradictory. Some studies found that resting CBF is similar between T2DM patients and controls (Tiehuis et al 2008; Rusinek et al 2015; Novak et al 2011), while others reported reduced CBF in patients with T2DM (Xia et al 2015; Novak et al 2006; Last et al 2007; Nagamachi et al 1994). The cross-sectional design of these studies however, did not allow to investigate the association between T2DM and changes in brain perfusion or structure and cognitive or mobility functions over time.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic exposure to hyperglycaemia may also lead to abnormalities in cerebral capillaries, such as basement membrane thickening [73,74]. Cerebral blood flow is reduced in experimental models of diabetes [75], but the effects of T2DM on cerebral perfusion in humans are less clear [76].…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…3 There are reports of changed cerebral blood flow in T2DM patients, 3 although a study with a larger sample found no significant differences when accounting for brain volume. 7 Recent studies examined the relation of cognition, brain volume, or white matter alterations with both cerebral blood flow and cerebrovascular reactivity and found no significant relationships. 8,9 Notably, a number of functional magnetic resonance imaging (fMRI) studies relied on BOLD (Blood Oxygenation Level-Dependent) signal 10 to indirectly measure neuronal activity and investigate neurophysiological impairment.…”
Section: Introductionmentioning
confidence: 99%